What Morality and Religion have in Common with Health? Pedagogy of Religion in the Formation of Moral Competence - Marek, Zbigniew (Journal of religion and health, 2021)
The aim of the article is to discuss how pedagogy of religion can contribute to the formation of moral competence and how this competence is in turn conducive to a new quality of life. Such analysis seems to be extremely important for modern educational theory. There are controversies concerning the role of morality in human life and its relationship with religion, and at the same time there is an increasing body of research that highlights the place and importance of religion in the formation of healthy individuals and societies. At the same time, the problem of the relationship between morality, religion and health is by no means new. The biblical writers already pointed out the connection between good and life, and between evil and death on the other hand. Both health and illness were taken to have their physical, inner, and spiritual dimensions. While Kulikova and Malchukova (2019) review the pedagogical and psychological subject literature, they lack references to the pedagogy of religion as a scientific discipline. This article aims to outline the Christian perspective on the formation of moral competence and its relationship with human health, understood as physical, mental, social and spiritual well-being. The understanding of this relationships is built on anthropological and transcendent foundations. Christian anthropological perspective means the acceptance of the so-called “personalistic norm.” Christian transcendent framework of moral education refers to the divine reality of the only God, the Creator and Redeemer of man. Moral competence is the result of moral education, which aims at engaging all human faculties—reason, emotions, and will—in discovering, accepting and internalizing values. One way of fostering moral competence based on the pedagogy of religion is to use the principles of the so-called pedagogy of accompaniment and testimony.